Assessment of the Ability of CMIP6 GCMS to Simulate the Boreal Summer Intraseasonal Oscillation Over Southeast Asia - Abatan, Abayomi A.; Collins, Matthew; Babel, Mukand S.; Khadka, Dibesh; De Silva, Yenushi K. (Frontiers in Climate, 2021)
The boreal summer intraseasonal oscillation (BSISO) plays an important role in the intraseasonal variability of a wide range of weather and climate phenomena across the region modulated by the Asian summer monsoon system. This study evaluates the strengths and weaknesses of 19 Coupled Model Intercomparison Project Phase 6 (CMIP6) models to reproduce the basic characteristics of BSISO. The models' rainfall and largescale climates are evaluated against GPCP and ERA5 reanalysis datasets. All models exhibit intraseasonal variance of 30–60-day bandpass-filtered rainfall and convection anomalies but with diverse magnitude when compared with observations. The CMIP6 models capture the structure of the eastward/northward propagating BSISO at wavenumbers 1 and 2 but struggle with the intensity and location of the convection signal. Nevertheless, the models show a good ability to simulate the power spectrum and coherence squared of the principal components of the combined empirical orthogonal function (CEOF) and can capture the distinction between the CEOF modes and red noise. Also, the result shows that some CMIP6 models can capture the coherent intraseasonal propagating features of the BSISO as indicated by the Hovmöller diagram. The contribution of latent static energy to the relationship between the moist static energy and intraseasonal rainfall over Southeast Asia is also simulated by the selected models, albeit the signals are weak. Taking together, some of the CMIP6 models can represent the summertime climate and intraseasonal variability over the study region, and can also simulate the propagating features of BSISO, but biases still exist.